Russian-Arab Military and Political Cooperation After the Arab Spring: Priorities and Prospects - Rakhmatullaev A. I.; Mannanova N. Kh. (Zien Journals, 2022)
Historically, Russian-Arab relations have been essentially different. There are two blocs of countries in the Middle East that traditionally have long-standing political and economic ties with Western countries that have retained their role in the region. At the same time, there is a bloc of countries with which Russia has strengthened relations after the "Arab Spring" in the Middle East. The countries that historically had relations with the Soviet Union, and then with Russia, include Syria, Egypt and Libya, and to a lesser extent Iraq and Yemen. And for a more detailed study of bilateral relations, in the author's opinion, Syria, Egypt and Libya should be highlighted. Since it was with these countries that Russia began to use a new approach in the military-political aspect and in the field of education. The relevance of this work is the increased role of Russia in international relations in the Middle East and North Africa, where, in accordance with the latest concept of the country's foreign policy, Russia intends to develop bilateral relations with the countries of this region and make a significant contribution to ensuring peace and security.
Keywords: Middle East; North Africa; politics; education